International perspective on research priorities and outcome measures of importance in the care of children with acute exacerbations of asthma: a qualitative interview study. Issue 1 (27th February 2023) - Gray, Charmaine S; Xu, Yao; Babl, Franz E; Dalziel, Stuart; Powell, Colin V E; Chong, Shu-Ling; Roland, Damian; Lyttle, Mark D; Fernandes, Ricardo M; Benito, Javier; Johnson, Mike; Yock-Corrales, Adriana; et al.
Abstract : Background: Acute exacerbations of asthma are common in children, however, treatment decisions for severe exacerbations are challenging due to a lack of robust evidence. In order to create more robust research, a core set of outcome measures needs to be developed. In developing these outcomes, it is important to understand the views of clinicians who care for these children in particular, views that relate to outcome measures and research priorities. Methods: To determine the views of clinicians, a total of 26 semistructured interviews based on the theoretical domains framework were conducted. These included experienced clinicians from emergency, intensive care and inpatient paediatrics across 17 countries. The interviews were recorded, and later transcribed. All data analyses were conducted in Nvivo by using thematic analysis. Results: The length of stay in hospital and patient-focused parameters, such as timing to return to school and normal activity, were the most frequently highlighted outcome measures, with clinicians identifying the need to achieve a consensus on key core outcome measure sets. Most research questions focused on understanding the best treatment options, including the role of novel therapies and respiratory support. Conclusion: Our study provides an insight into what research questions and outcome measures clinicians view as important. In addition, information on how clinicians define asthma severity and measure treatment success will assist with methodological design in future trials. The current findings will be used in parallel with a further Paediatric Emergency Research Network study focusing on the child and family perspectives and will contribute to develop a core outcome set for future research.